The current state of functioning and resourcefulness of individuals during turbulent times - O.A. Panchenko; A.V. Kabantseva; I.A. Serdyuk (Medičnì Perspektivi)
The purpose of the work was a study of the current functioning and resourcefulness of the adult population of Ukraine among different age groups amidst turbulent changes. Conducted by the State Institution "Scientific and Practical Medical Rehabilitation and Diagnostic Centre of the Ministry of Health of Ukraine," the study surveyed 1216 respondents residing in eastern, central, and western Ukraine. Methodological basis of the study was observation, interviews, questionnaires, and testing. The study examined topical  aspects of turbulent changes on respondents, their current psycho-emotional state, information needs, sources of information, daily functioning, subjective assessment of life quality, presence of anxiety, depression, aggression, and the role of joy as a source of resilience during wartime in Ukraine. The results of the study showed that people in late adulthood were more likely to be anxious about hostilities and the socio-economic situation in the country compared to young adults (p<0.001). Furthermore, the study found a positive correlation between age and the percentage of people reporting high anxiety about the country's socio-economic situation (p<0.001). These worrying situations resulted in changes in daily functioning, particularly chronic daytime fatigue  and drowsiness (p=0.069), feelings of dissatisfaction with oneself (p=0.223), manifestations of aggression towards oneself (p=0.603) and loved ones (p=0.148). Interestingly, early adulthood individuals showed more aggression towards other people compared to late adulthood individuals (p=0.013). The study also showed that feelings of joy serve as a resource for coping with war trauma and are an important indicator of mental health.